EVALUASI PROGRAM PEMBERDAYAAN MASYARAKAT PLUS PADA BIDANG KESEHATAN DI MASA PANDEMI COVID – 19 KELURAHAN BUJEL KECAMATAN MOJOROTO KOTA KEDIRI - Muhammad Alif Izzuddin; Tjitjik Rahaju (Universitas Negeri Surabaya, 2022)
The government of Kediri city publishes mayor of Kediri regulation number 23 of 2020 about technical guidlines for comunity empowerment plus (Prodamas Plus). Through this regulation, the government of Kediri city want to handling about COVID – 19 in Kediri region. So, the implementation about Prodamas Plus has main focus in health issues. Then, alocation of prodamas plus in 2021 in health reach until 50% for make equipment in health like pay for national health insurance, buy some equipment for health, and supplementary feeding. This research use qualitative approach with type of research is descriptive. Focus of research in evaluation of Prodamas Plus and use evaluation theory from William N. Dunn that contain six indicators, there are efectiveness, efficiency, adequacy, distribution, responsiveness, and accuracy. Result of research show that implementation Prodamas Plus in health has been qualified for six indicator about policy evaluation. Problem in prodamas plus is lack of coast, so, people in Bujel region expanding endownment to close the deficiency. Author give the suggetions that alocation for prodamas plus can be added to complete essential needs for people. Then, government of Bujel can accomodate needs for Bujel community which can be budgeted in Prodamas Plus to increase participation of community to save their environment in situation of COVID – 19 pandemic